O sistema tributário da China: Um olhar a partir do Brasil - Pedro Humberto Bruno De Carvalho Junior; Ticiana Gabrielle Amaral Nunes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This study describes China's tax system and the applied tax policies against the covid-19 crisis, which were the Value Added Tax (VAT) deferral and Corporate Income Tax (CIT) deductions. China has a tax system following international standards, having a unified and decentralized tax agency. The system has a VAT with simplified rates, Excise Taxes and a dual Personal Income Tax (PIT) system, progressive on labor and proportional on dividends and capital gains. The social contributions have been increasingly comprehensive but focused on formal workers. On the other hand, the local taxes are complex, existing a myriad of taxes on real estate transactions and urban fees. In addition, it lacks a recurrent tax on immovable property, a tax on inheritances, and a net wealth tax. The study concludes that China should adopt more progressive tax policies due to the growing inequality, exacerbated after the post-pandemics crisis.
Keywords: N45; H20; H71; H83; 330; China; taxation; public finances; fiscal policies; federalism; covid-19